The Effect of Profitability, Funding Decisions and Cash Flow Operations on Financial Distress with Financial Risk as a Mediating Variable and Financial Flexibility as a Moderating Variable in the Basic Industrial and Chemical Sector Listed on the Indonesian Stock Exchange - Djuma’iyah; Tri Ratnawati; Ida Ayu Sri Brahmayanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study was conducted with the aim of analyzing the effect of profitability, funding decisions and cash flow operations on financial distress through financial flexibility with financial risk as mediation. The population used in this study were Basic Industry and Chemical Sector Manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 - 2023 which received a special notation category X, namely listed on a special monitoring board with a total sample of 20 companies. Hypothesis testing in this study was carried out with a Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results showed that profitability and financial risk directly have a significant effect on financial distress. The cash flow operation funding decision has no significant effect on financial distress. Through financial risk, profitability is proven to have a significant effect on financial distress, while funding decisions and cash flow operations have no significant effect on financial distress. Other results show that financial flexibility is not able to moderate the effect of profitability, funding decisions and cash flow operations on financial distress